Leveduras e bactérias lácticas associadas às chichas, bebidas tradicionais produzidas no Equador - Fernanda Barbosa Piló (2014)
The chicha are the oldest traditional beverage of South America. These traditional beverages are produced mainly from maize, but can be made with other raw materials. The chichas have been present in many indigenous cultures, notably in the Inca culture, playing a key role in religious celebrations. Despite the historical and cultural importance of chichas and the fact that they are still present in food habits of the populations of several Latin American countries, there are few studies evaluating the microbial diversity of these beverages. This study aimed to identify yeasts and lactic acid bacteria associated with different chichas from Ecuador, by molecular methods, as well as evaluate the physical-chemical parameters of pH, total reducing sugars, ethanol and lactic acid of beverages. A total of forty-seven samples of chichas were collected in two regions of Ecuador [one chicha of rice, two chichas of morocho (variety of white maize), three chichas of seven grains (seven grain varieties), five chichas of yuca (cassava) and thirty-six chichas of jora (maize malted)]. The yeasts and lactic acid bacteria (BAL) were isolated in 45 and 42 samples, respectively. The counts of lactic acid bacteria (1.93x107 to 6.97x108 cfu/mL) were higher than those of yeasts (3.0x105 to 1.12x108 cfu/mL). From the 116 BAL isolates 11 different species were identified. Lactobacillus fermentum and L. plantarum were the most prevalent species of BAL being found in 61.1% and 55.5% of samples, respectively. The 295 yeast isolates obtained were shown to belong to 30 species. Saccharomyces cerevisiae is the most prevalent species of yeast, being found in 78.7% of samples, ranging from 3.33 x 104 to 8.67x107 cfu/mL. Other yeasts were also found in chichas included Torulaspora delbrueckii, Hanseniaspora spp., Pichia kudriavzevii and Galactomyces geotrichum. Among the 122 isolates of S. cerevisiae, 69 different molecular profiles of mitochondrial DNA (mtDNA) have been found. A chicha of jora analyzed at different fermentation times (0 to 5 days) presented 16 isolated from S. cerevisiae, which have been grouped into four different profiles. Only one of these four profiles could be found during all times of fermentation analyzed. The chicha of seven grains showed the greater diversity of S. cerevisiae strains per sample based on mtDNA restriction profiles. However, it was also the beverage with the highest number of S. cerevisiae isolates per sample. The pH values obtained, ranging from 2.62 to 4.15, were similar to those found for other traditional fermented beverages. The amount of total reducing sugars (TRS) varied significantly, from 1.63 g/L to 38.68 g/L, possibly due to the variety of ingredients and uncontrolled fermentation. The lactic acid concentration values ranged from not detectable to 6.90 g/L and it was found in 32 samples. The ethanol was found in 25 samples in small amounts, ranged from undetectable amounts to 5.87% v/v. The different chichas of Ecuador can be considered acid fermented beverages produced from a combination of lactic acid bacteria, mainly lactobacilli species, with Saccharomyces cerevisiae and non-Saccharomyces yeasts.